Meningkatkan Hasil Belajar Siswa Melalui Model PBL Mata Pelajaran Pendidikan Agama Katolik Fase B SDN 25 Tahlut Tahun Pelajaran - Lusia Emiliana; Anselmus Yata Mones; Benediktus Sutarjo (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research aims to determine the increased learning outcomes in Catholic Religious Education subjects for grade 4 students at SDN 25 Talhut. This research uses a classroom research method carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The average score students obtained when using the PBL model in the first cycle was 69%, and in the second cycle, it was 85%, according to the research results for the two processes. If the PBL learning model is implemented well and consistently, it will improve student learning outcomes.